About clasp’s bearing capacity of thermoplastic removable partial dentures - Grigorenko, Ya. M.; Grigorenko, A.Ya.; Nespryadko, V.P.; Tormahov, N. N; Zakurko, S. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The method of calculation of the bearing capacity of removable partial dentures, whose basis and clasps are made of thermoplastics, is proposed. The calculation includes the determination of the specific pressure of a clasp on the abutment, internal forces, and stresses in the weakest section of a clasp. The calculations allow one to select the optimal size of a clasp in order to create the necessary holding force of a prosthesis with its enough strength.